The role of tumor molecular subtypes in formation of personalized approach to the theatment of the breast cancer - Bondarenko I.N.; Elhajj Mohammad H.; Chebanov K.O.; Phokhach A.V.; Bondarenko Y.N. (Medičnì Perspektivi)
Extreme heterogeneity of breast cancer (BC) is considered to be one of the reasons that affects the success of treatment. According to current classifications, there are 4 molecular subtypes (MS). The basis for subtypes division is immunohistochemical testing of tumor cell receptors - estrogen (ER), progesterone (PR), HER2-neu and Ki-67. The doctrine of the tumor MS was the basis for the individualization of therapeutic tactics in patients with breast cancer. It was studied that luminal A subtype is the most common and the most favorable, with hormone therapy being a highly effective treatment method. Luminal B subtype, HER2 - positive and triple negative MS is characterized by a high aggressiveness, worse survival rate of patients and better prognostic effect of chemotherapy. The importance of determining the level of Ki-67 for assessment of tumor aggressiveness was revealed. Significant differences in receptor status of the primary tumor and metastases were proven. Data on the impact of changes in receptor status of the tumor prognosis are ambiguous and need further study. The use of targeted agents in the treatment of HER2 + patients can significantly improve treatment outcomes, turning this MS from historically aggressive subgroup to quite favorable.